Identity in Academic Writing Established by Indonesian vs Non-Indonesian Writers - Afandi, Titah; Roselani, Ni Gusti Ayu (Fakultas Bahasa dan Seni UNP, 2024)
Academic writing in the form of international journal articles is primarily read and used as references for many academic communities. Since the writers of an international journal are from different backgrounds and countries, their works have some differences in terms of writing styles. How the writers show authorial identity and authority through the texts is one of the aspects that causes the differences. This study investigates how Indonesian and non-Indonesian writers established their identities in academic writing. This study used the descriptive qualitative research method. Hyland’s (2005b) stances theory (hedges, boosters, attitude makers, and self-mentions) was applied as the research approach with the help of the AntConc corpus toolkit to analyze the data that were collected from an international journal. The results and discussion show similarities and differences regarding Hyland’s stances in journal articles written by Indonesian and non-Indonesian writers. The results and discussion reveal both similarities and differences in how Indonesian and non-Indonesian writers convey authorial identity and authority through their texts.